Efektifitas Komsumsi Ikan Kembung Terhadap Perubahan Kadar Hemoglobin Pada Ibu Hamil Dengan Anemia - Ulfa Sa’idah; Nila Widya Keswara (Journal of Innovative and Creativity, 2025)
Anemia during pregnancy is considered a national concern as it mirrors the social and economic well-being of the population and significantly impacts the quality of human capital. It is often referred to as a “potential risk to both mother and child.” This study employed a qualitative approach with a Quasi-Experimental design, specifically utilizing a one-group pretest-posttest format. An initial assessment (pretest) was conducted prior to the intervention, followed by a post-intervention assessment (posttest) to evaluate any changes resulting from the treatment. The sampling method for this research used a non- probability sampling method with total sampling. To determine the sample in this research, the Slovin formula was used. The results of hypothesis testing using the paired t test obtained p(sig.) 0.000 <0.05, then H1 was accepted and H0 was rejected, meaning there was a significant difference in the mean value of the pretest score (Hb level before being given mackerel) and posttest results (Hb levels after being given mackerel), so it can be concluded that there is an influence of consumption of mackerel on change in hemoglobin level in pregnant women with anemia. The findings of the study indicate that anemia in pregnant women is caused by multiple factors, with one key contributor being inadequate iron levels in the body, along with a reduction in red blood cell count or a lowered hemoglobin concentration in the bloodstream. During pregnancy, anemia occurs because pregnant women experience hemodilution (dilution).